Effects of Konjaku Flour on the Gut Microbiota of Obese Patients - Li, Yu; Kang, Yongbo; Du, Yuhui; Chen, Minghui; Guo, Liqiong; Huang, Xinwei; Li, Tingting; Chen, Shi; Yang, Fan; Yu, Fubing; Hong, Jingan; Kong, Xiangyang (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Gut microbiota have been thought to play a role in the emergence of obesity and metabolic disorders, thus dietary fiber may be an effective strategy for the management of obesity by modulating the gut microbiota. The aim of the present study was to investigate the effects of konjaku flour (KF) supplementation on treating obesity and regulating intestinal microbiota in obese adults. Methods In a 5-week, randomized, double-blind, place-controlled trial, sixty-nine obese volunteers aged 25 to 35 with body mass index ≥28 kg/m2 were randomly assigned to receive KF or placebo (lotus root starch). Obesity index, blood parameters, and gut microbiota were analyzed. Results KF remarkably reduced the body mass index (BMI), fat mass, percentage body fat (PBF), serum triglyceride (TG), glycated hemoglobin A1c (HbA1c), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels in the patients (p <0.05 or p <0.01). Meanwhile, high-throughput sequencing and bioinformatics analysis showed that the konjac flour treatment notably increased the α-diversity and changed the β-diversity of intestinal microflora in patients (p <0.01). Moreover, konjac flour could also evidently increase the abundance of some of the beneficial microorganisms related to obesity of patients, such as Lachnospiraceae, Roseburia, Solobacterium, R. inulinivorans, Clostridium perfringens, and Intestinimonas butyriciproducens, and reduce the abundance of the harmful microorganisms, such as Lactococcus, Bacteroides fragilis, Lactococcus garvieae, B. coprophilus, B. ovatus, and B. thetaiotaomicron (p <0.01). Specifically, C. perfringens was significantly negatively correlated with serum total cholesterol (TC) (p <0.01). Conclusion These results suggested that KF can achieve positive effects on treating obesity, which manifest on reducing BMI, fat mass, blood glucose, and blood lipid, improving hepatic function, and also regulating intestinal microfloral structure. Therefore, changes in gut microbiota may explain in part the effects of KF.